Ensaios pré-clínicos com extratos de plantas medicinais do semi-árido nordestino: contribuição para o tratamento de infecções da cavidade bucal - Silva, Maria Suênia Pereira da (2011)
The World Health Organization (WHO) has encouraged the use of traditional medicine integrated with modern medicine in health systems. In Brazil there is already a National Policy on Herbal and Medicinal Plants and one of its goals is to provide herbal and / or herbal medicines to health of public service. In this context, the objective was to evaluate in vitro the antimicrobial activity of medicinal plants of the semi-arid Northeast over microorganisms from the oral cavity, and to verify in vivo the presence of acute toxicity and mutagenic action of hydroalcoholic extracts from that presented the largest halos antimicrobial growth inhibition. Five extracts were produced from each plant studied and performed a microbiological screening. The antimicrobial activity was evaluated by agar diffusion method, using the technique of the cylinder. The acute toxicity tests were conducted using rats and Artemia salina of larva. For the mutagenicity test was used the micronucleus test. Plants with improved microbial activity was mainly Schinopsis brasiliensis Engl. and Ximena americana L., which were produced nebulized extracts, with the objective of performing the Minimum Inhibitory Concentration (MIC). Only the extract of S. brasiliensis produced in MIC which were only observed against the Staphylococcus aureus and Pseudomonas aeruginosa. Halos antimicrobial growth inhibition were not observed in Streptococcus oralis and Enterococcus faecalis, probably because the active ingredients to which these bacteria are sensitive, were destroyed during the process of spraying the extract. The same occurred with the dry extracts of X. americana L. not present any antimicrobial activity against the strains tested. In acute toxicity test with rats results indicated that extracts of S. brasiliensis administration showed low toxicity. In the toxicity test with A. salina, these extracts were toxic. Micronucleus test in extracts of S. brasiliensis showed mutagenic activity in mice. Thus, in concentrations that were used, extracts of S. brasiliensis and X. americana showed antimicrobial activity, low toxicity in rats, were toxic to A. salina and mutagenic for mice.